Investigation the need to teach the characteristics of the development of parliamentarism in Latin America as part of education - Lvovna Norden, Larisa (2021)
The article highlights the history and features of parliamentarism development in the Latin America countries. In addition, the need for training on the subject and the effect of increasing students and educators’ awareness in this field is examined. This process was lengthy, replete with the examples of various social groups, political trends and parties struggle intensity increase. Since the beginning of the 19th century, there have been almost no favorable conditions for the practical implementation of democratic government in the countries of Latin America, and the institutionalization of the party system has not taken place yet. However, there have been exceptions to the general rule in the history of Latin America. Chile and Argentina were such an example. The success of democratic transformations in the countries of the region depended on various reasons: a) whether the country had a democratic experience in its past; b) the conditions for the political and economic development of this country to develop representative institutions in the future; c) the importance of the parties in the political course development and the adoption of state decisions. The results of democracy and parliamentarism development in the states of Latin America are rather complicated by the turn of the 20th and 21st centuries. On the one hand, the last decades of the XX-th century and the beginning of this century was marked by the democratization of political life, reforms, and the replacement of military regimes with civilian governments. Since the beginning of the 60-ies, they started the process of democratization and formation of independent island states in the Caribbean and Central America. Despite the successful development of the economy, culture, education, the presence of a large middle class in Argentina, the military governments overcame civilian ones in the 30-70-ies. Therefore, it is needed to consider this aspect as a part of education system to improve the educators’ level.